2021
DOI: 10.1080/07060661.2021.1936649
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the expression and interaction of Rph genes conferring seedling and adult plant resistance to Puccinia hordei in barley

Abstract: Leaf rust caused by Puccinia hordei is a major disease of barley and is best managed by deploying effective resistance genes. The effect of post-inoculation temperature [18 ± 2°C (low), 22 ± 2°C (mid), or 26 ± 2°C (high)] on the expression of a selection of known all stage resistance (ASR) Rph genes and their interaction in combination with the adult plant resistance (APR) gene Rph20 were investigated in barley. Rph1.a and Rph2.b expressed best at higher temperatures whereas Rph4.d lost its effectiveness at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mecknes Maroc ( Elmansour et al, 2017 ). Very recently, Singh et al (2021) reported on the interaction of an APR ( Rph20 ) and an ASR ( Rph5.e ) gene conferring resistance to P. hordei virulent pathotype. In soybean, the resistance of accession JS 95-60 to the fungus Colletotrichum truncatum was also regulated by the interactions of two major genes in complementary fashion ( Nataraj et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mecknes Maroc ( Elmansour et al, 2017 ). Very recently, Singh et al (2021) reported on the interaction of an APR ( Rph20 ) and an ASR ( Rph5.e ) gene conferring resistance to P. hordei virulent pathotype. In soybean, the resistance of accession JS 95-60 to the fungus Colletotrichum truncatum was also regulated by the interactions of two major genes in complementary fashion ( Nataraj et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, combinations of various “defeated” genes providing residual effects have been reported in multiple crops against different pathogens ( Nass et al, 1981 ; Royer et al, 1984 ; Brodny et al, 1986 ; Li et al, 1999 ). The interaction of an APR and an ASR gene conferring resistance to P. hordei virulent pathotype has also been reported ( Singh et al, 2021 ). When being singly deployed, both the ASR gene Rph5.e and the APR gene Rph20 are ineffective against the pathotype 220 P+ +Rph13 at the seedling stages.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that barley is the fourth largest global grain crop, after wheat, rice, and corn. Barley seeds have moderate amounts of protein, phosphorus, and calcium, as well as small amounts of B vitamins [7]. Furthermore, since the carbohydrate content in barley seeds is high, they are commonly used in breads, soups, stews, and other health products [8].…”
Section: Introductionmentioning
confidence: 99%